Study of graft survival rates of renal transplants in Cairo University Hospitals - Mohamed G Saadi; Sahier O El-Khashab; Rabab M.A. Mahmoud (SpringerOpen, 2016)
Background Many factors and events can complicate the outcome of renal transplantation and can eventually lead to progressive renal dysfunction and graft failure. We aimed in this study to identify the risk factors for the entire course after transplantation, and then to analyze the relative impact of these risk factors on short-term and long-term graft survival in our patients. Patients and methods This analytical retrospective study was conducted at the King Fahd Unit, the Faculty of Medicine, Cairo University, on 104 patients for the study of 1-year graft survival, though 43 patients were followed-up for 3 years for the study of 3-year graft survival. Serum creatinine was used to evaluate the renal function; graft dysfunction was defined as serum creatinine more than 2.5 mg/dl. Survival analysis was carried out by using the Kaplan-Meier survival curve estimation. To predict the value of graft survival after 5 years, regression analysis was used. Results In our study, the overall graft survival rates were 88.6 and 76.7% at 1 and 3 years, respectively. The corresponding overall patient survival rates were 89.4 and 79.1% at the first and third years after transplant. Our study showed that among the long list of predictors for graft outcome variables, factors that had a significant impact on outcome by Kaplan-Meier analysis included donor's age, primary immunosuppression, and serum creatinine 1 month after transplant. There was a greater rate of graft dysfunction with the presence of hypertension and hepatitis C virus but these results did not reach statistically significant values. Conclusion Old donor's age, primary immunosuppression, and serum creatinine 1 month after transplant are the most effective factors on graft survival in kidney transplantation. Whatever the cause, graft dysfunction should be treated early and aggressively.